DEIKSIS DALAM FILM SNOW WHITE AND THE SEVEN DWARFS KARYA WALTER ELIAS DISNEY (SUATU ANALISIS PRAGMATIK) - Lumawir, Hesty N (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACTS Pragmatics is the study of the relations between language and context that are basic to an account of language understanding. The most obvious single way in which the relationship between language and context is reflected in the structures of the language themselves through the phenomenon of the deixis. The research questions of this investigation are what types of deixis are found in the film Snow White and The Seven Dwarfs and how the use of deixis in the film. The method used in the research is descriptive method. The data are identified and analyzed descriptively. The data are analyzed based on the theory of Levinson. The result shows that there are five types of deixis found in this film. Those are person deixis, place deixis, time deixis, discourse deixis, and social deixis, whereas the usages of deixis found in the film are symbolic and gestural usage. It is espected that this research will help the students and other readers to learn the pragmatic aspects, especially on deixis. Â Keywords: Deixis, Film: Snow White and The Seven Dwarfs. Pragmatic Analysis.